Histological and Morphometric Comparison of Lactating Mammary Glands in Pigs Depending on Their Location - Svätoslav Hluchý; Róbert Toman; Mária Adamkovičová; Michal Cabaj (Scientific Papers Animal Science and Biotechnologies, 2023)
In this paper we described a morphometric comparison of lactating mammary glands of pigs, depending on their location. As experimental animals were used five pig breeds White Meat at the age of 24 months. Anatomical dissection and sampling of the mammary glands of thoracic, abdomen and pubic udders for histological processing and subsequent quantitative morphometric evaluation were taken after killing the animals. It was found that glandular parenchyma, stroma connective tissue and adipose tissue in the mammary glands of the thoracic, abdomen and pubic udders quantitative evenly distributed regardless of udder location. It was found that the epithelium, lumen, collagenous tissue and loose connective tissue in the mammary glands of the thoracic, abdomen and pubic udders of swine quantitative evenly distributed regardless of their location. The average size of glandular alveolar parenchyma varied from 122.46 μm ± 45.73 μm to 138.47 ± 33.16 μm, which were not found statistically significant differences of the average size of alveoli between udders. The average abundance of the alveoli in the 1 cm3 of tissue of the mammary glands was 226 933, 08 161 ± 136.27, because not all the alveoli were the same size. There was no difference in abundance of the alveoli between udders. It found the percentage of small, medium and large alveoli. Also, the relative volume of the walls (epithelium) and cavity (lumen) alveoli is balanced in all udders and unrelated to their location. Negative correlations between the abundance and size of the alveoli were found.